Knock-down of YME1L1 induces mitochondrial dysfunction during early porcine embryonic development - Zhou, Dongjie; Sun, Ming-Hong; Jiang, Wen-Jie; Li, Xiao-Han; Lee, Song-Hee; Heo, Geun; Choi, Jungseok; Kim, Kwan-Suk; Cui, Xiang-Shun (Frontiers in Cell and Developmental Biology, 2023)
YME1L1, a mitochondrial metalloproteinase, is an Adenosine triphosphate (ATP)-dependent metalloproteinase and locates in the mitochondrial inner membrane. The protease domain of YME1L1 is oriented towards the mitochondrial intermembrane space, which modulates the mitochondrial GTPase optic atrophy type 1 (OPA1) processing. However, during embryonic development, there is no report yet about the role of YME1L1 on mitochondrial biogenesis and function in pigs. In the current study, the mRNA level of YME1L1 was knocked down by double strand RNA microinjection to the 1-cell stage embryos. The expression patterns of YME1L1 and its related proteins were performed by immunofluorescence and western blotting. To access the biological function of YME1L1, we first counted the preimplantation development rate, diameter, and total cell number of blastocyst on day-7. First, the localization of endogenous YME1L1 was found in the punctate structures of the mitochondria, and the expression level of YME1L1 is highly expressed from the 4-cell stage. Following significant knock-down of YME1L1, blastocyst rate and quality were decreased, and mitochondrial fragmentation was induced. YME1L1 knockdown induced excessive ROS production, lower mitochondrial membrane potential, and lower ATP levels. The OPA1 cleavage induced by YME1L1 knockdown was prevented by double knock-down of YME1L1 and OMA1. Moreover, cytochrome c, a pro-apoptotic signal, was released from the mitochondria after the knock-down of YME1L1. Taken together, these results indicate that YME1L1 is essential for regulating mitochondrial fission, function, and apoptosis during porcine embryo preimplantation development.